The impact of R&D incentives in the competitiveness of Portuguese SMEs. (11th March 2020) - Abrantes, Liliana M.; Pereira, Elisabeth T.; Botelho, Anabela
The aim of the present study is to evaluate whether the European incentives received by SMEs to invest in R&D projects make these companies more competitive. With this purpose, was collected data from 151 SMEs, which received subsidies for R&D, from the COMPETE - operational program competitiveness factors, during the period from 2007 to 2013. According to the economic literature, the return on R&D investment made by companies is not immediate, and the results on the competitiveness may not be observed in the early years. Using an econometric methodology of panel data, this study concludes that the incentives reflect a positive effect on SMEs' competitiveness only in the third year after the R&D investment.